The Law of Bad Smells: Making and Adjudicating Offensiveness Claims in Contemporary Local Law. Issue 2 (August 2019) - Valverde, Mariana
Abstract: The sense of smell seems to have resisted the kind of objective measurement process that might have facilitated settling competing claims about offensive smells by applying a general rule or standard. As a result, authorities, including courts, cannot avoid making subjective judgements of taste. A nuisance lawsuit out of Ontario regarding a mushroom farm, or rather its smells, is used here as one source of material about the difficulties of adjudication in this subfield of the "law of the senses." Attention is also paid to a curious quasi-judicial entity, Ontario's Normal Farm Practices Protection Board, charged with resolving, mainly through mediation, disputes about farm smells between farmers and non-farming neighbours. Overall, the article shows that the ex post facto, situated and complaint-driven logic of nuisance that nineteenth-century law used to govern offensive noises as well as nasty smells, and which left plenty of room for subjective judgements of taste, keeps reappearing in the present day. Nasty smells seem particularly impervious to modernization, that is to being managed through objective measurement and preventive regulation. Résumé: L'odorat semble avoir résisté au processus de création de mesures objectives où l'on applique une règle ou une norme générale. Ce processus aurait pu faciliter la règlementation relative aux réclamations concurrentes sur les odeurs offensantes. Par conséquent, les autorités, y compris les tribunaux, ne peuvent éviter de porter des jugements subjectifs. Une poursuite pour nuisance, qui se déroule en banlieue de l'Ontario, et se rapportant à une champignonnière, ou plus précisément ses odeurs, est d'ailleurs utilisée dans cet article afin d'illustrer les difficultés dans la prise de décision judiciaire relativement au droit des sens. Une attention particulière est également portée à la Commission de protection des pratiques agricoles normales de l'Ontario, une curieuse entité judiciaire qui est chargée de régler, principalement par la médiation, les différends concernant les odeurs agricoles entre les agriculteurs et leurs voisins non-agriculteurs. Dans l'ensemble, le présent article montre que la logique de nuisance a posteriori, située et fondée sur les plaintes, qui était utilisée dans le droit du XIXe siècle afin de régir les bruits offensants et les mauvaises odeurs, et qui laissait une large place aux jugements subjectifs, ne cesse de réapparaître dans le monde actuel. Les odeurs désagréables semblent, en ce sens, particulièrement insensibles à la modernisation, c'est-à-dire à la gestion par des mesures objectives et à une réglementation préventive.